1999
DOI: 10.1046/j.1365-2044.1999.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Near‐miss’ hyperkalaemic cardiac arrest associated with rapid blood transfusion

Abstract: SummaryA case is presented in which a relatively modest blood transfusion resulted in acute hyperkalaemia with a 'near-miss' cardiac arrest. While transfusion-related hyperkalaemia usually occurs in association with massive transfusions, several factors may have increased the risk of such an acute reaction. A high index of suspicion is required, especially in patients with risk factors. Anaesthetists should not be lulled into a false sense of security simply because modest volumes of blood are being transfused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…It is now well documented that the potassium concentration of 7‐day‐old blood units (packed RBCs stored in AS‐1) is around 23 mmol L −1 , whereas that of the 42‐day‐old blood units, in AS‐1, is in the 50 mmol L −1 range (Vengelen‐Tyler, 1999). Potassium concentrations as high as 70 mmol L −1 have been reported in 28‐day‐old, irradiated blood units stored in SAG‐M (De Silva & Seghatchian, 1994; Carvalho & Quiney, 1999). Campbell (1955) has reported that 7‐day‐old blood units used in exchange transfusions of infants with haemolytic disease have potassium levels in the range of 6·5–8 mmol L −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well documented that the potassium concentration of 7‐day‐old blood units (packed RBCs stored in AS‐1) is around 23 mmol L −1 , whereas that of the 42‐day‐old blood units, in AS‐1, is in the 50 mmol L −1 range (Vengelen‐Tyler, 1999). Potassium concentrations as high as 70 mmol L −1 have been reported in 28‐day‐old, irradiated blood units stored in SAG‐M (De Silva & Seghatchian, 1994; Carvalho & Quiney, 1999). Campbell (1955) has reported that 7‐day‐old blood units used in exchange transfusions of infants with haemolytic disease have potassium levels in the range of 6·5–8 mmol L −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The important factors that play a role in the acute alterations due to potassium are the rate of infusion, the amount transfused and the site of infusion (Carvalho & Quiney, 1999). In our case, where the baby suffered from acute extensive blood loss, rapid transfusion of packed RBCs was an urgent requirement, and 120 mL of blood was pushed through the central line.…”
Section: Discussionmentioning
confidence: 99%
“…However, rapid infusion of large volumes of RBCs into neonates or patients with cardiac, hepatic, or renal dysfunction mandates close monitoring. [1011]…”
Section: Introductionmentioning
confidence: 99%
“…The Airtraq has a similar profile to the Bullard laryngoscope and we hope that it will be as successful in grades 3 and 4 Macintosh laryngoscopy [2]. Early indications are good [3].…”
Section: A Replymentioning
confidence: 92%